2011
DOI: 10.4103/0970-0218.84128
|View full text |Cite
|
Sign up to set email alerts
|

Mass measles rubella immunization campaign: Bhutan experience

Abstract: Background:Bhutan has attained universal child immunization since 1991. Since then, immunization coverage is maintained at high level through routine immunization, periodic National Immunization Days, and mop up campaigns. Despite high immunization coverage, every year, significant numbers of clinically suspected measles cases were reported.Objective:To assess the cause of continuing high “suspected measles cases” and take appropriate public health measures.Materials and Methods:Febrile rash outbreaks occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…In a study conducted by Chuang et al at Hong Kong showed a very high coverage (90%) among children in the age group of 6-11 years. 7,13 The study observed not much gender bias the vaccine recepients (boys: 52.3%, girls: 47.7%) had received the vaccine which is analogous to the coverage observed by Sayed El, et al at Egpt. (boys: 50.9%, girls: 49.1%).…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…In a study conducted by Chuang et al at Hong Kong showed a very high coverage (90%) among children in the age group of 6-11 years. 7,13 The study observed not much gender bias the vaccine recepients (boys: 52.3%, girls: 47.7%) had received the vaccine which is analogous to the coverage observed by Sayed El, et al at Egpt. (boys: 50.9%, girls: 49.1%).…”
Section: Discussionsupporting
confidence: 63%
“…Karnataka was selected in the first phase of the campaign. 3,13,20 In the present study, out of 312 families covered only 275 families (88%) were aware about the MR campaign. These families had received information from the health workers (50%), school authorities (43.3%) and mass media (2.6%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations